Postcard to Georg Bredig from Georg Lunge, February 1910 - Lunge, Georg (1910)
Postcard sent from Georg Lunge (1839-1923) to Georg Bredig (1868-1944). Lunge was a German chemist and professor at the University of Zurich. Lunge's original contributions cover a very wide field, dealing both with technical processes and analysis. In addition, he was a voluminous writer, enriching scientific literature with many standard works. His treatises Coal Tar and Ammonia, Destillation des Steinkohlentheers, and Sulphuric Acid and Alkali, established his position as the highest authority on these subjects, while the Chemische-Technische Untersuchungs-Methoden, to which he contributed, testified to his researches in technical analysis.
Keywords: Bredig, Georg, 1868-1944; Lunge, Georg, 1839-1923